2020
DOI: 10.4102/sajhrm.v18i0.1411
|View full text |Cite
|
Sign up to set email alerts
|

The year-on-year analysis of the relationship between chief executive officer remuneration and state-owned company performance in South Africa

Abstract: Orientation: Executive remuneration remains very much at the centre of academic and policy debates. There seems to be a lack of consensus on the origins of the substantial increase in executive remuneration.Research purpose: This study aimed to further explore the relationship between chief executive officer (CEO) remuneration and state-owned company (SOC) performance by investigating the year-on-year behaviour of the relationship. The observed trends regarding the direction and strength of the relationship in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Many researchers have analyzed the impact of managerial pay on business performance and found that there are conflicting results. They are based on the fact that there is (Bussin and Modau, 2015;Bezuidenhout, 2016;Uyanik, 2017) or there is not (Gigliotti, 2013;Luo, 2015;Rahman 2017) a significant relationship between company performance. What is significant about this period is that there was a decrease in individual performance and layoffs were necessary (Groysberg et al, 2021).…”
Section: Responsible Rewarding Of Top Managers In the Field Of Touris...mentioning
confidence: 99%
“…Many researchers have analyzed the impact of managerial pay on business performance and found that there are conflicting results. They are based on the fact that there is (Bussin and Modau, 2015;Bezuidenhout, 2016;Uyanik, 2017) or there is not (Gigliotti, 2013;Luo, 2015;Rahman 2017) a significant relationship between company performance. What is significant about this period is that there was a decrease in individual performance and layoffs were necessary (Groysberg et al, 2021).…”
Section: Responsible Rewarding Of Top Managers In the Field Of Touris...mentioning
confidence: 99%
“…Chief Executive Officer (CEO) compensation is commonly known a combination of financial and non-financial benefits that consists of fixed salary and short-and long-term incentives (Bezuidenhout, 2016). Number of studies have focused on the relationship between CEO compensation and capital structure; however, insufficient attention has been paid to those association with non-financial firms in the European economy.…”
Section: Ceo Compensationmentioning
confidence: 99%
“…Other previous studies (Bezuidenhout & Bussin, 2020;Marimuthu & Kwenda, 2019) on the CEO of an SOE were not focussing on the challenges the CEOs face when executing a turnaround strategy in the SOE but rather on the impact the CEOs' remuneration has on performance. Fourie (2014) analysed the role of four SOEs in South Africa and discussed their financial contribution and performance.…”
Section: Introductionmentioning
confidence: 99%